Antioxidant enzyme system modulation by dietary palm oils, palm kernel oil and soybean oil in laying hens - Izuddin, Wan Ibrahim; Loh, Teck Chwen; Nayan, Nazri; Akit, Henny; Foo, Hooi Ling; Noor, Ahmadilfitri Md (Multidisciplinary Digital Publishing Institute, 2023)
Palm-based oils (palm oil and kernel oil) and soybean oil have unique fatty acid and antioxidant profiles based on the compounds present in them. Hence, this study elucidated the antioxidant properties of crude palm oil (CPO), red palm oil (RPO), refined palm oil (RBD), palm kernel oil (PKO) and soybean oil (SBO) and the influence of dietary oils on blood lipid profiles, tissue fatty acid deposition and the expression of hepatic lipid and lipoprotein metabolism genes in laying hens. The oils were analyzed for color, beta-carotene, free fatty acid and acid value, phenolic content and lipid peroxidation. In an in vivo trial, 150 laying hens were allotted into five groups and supplemented with either CPO, RPO, RBD, PKO or SBO for 16 weeks. High antioxidant compounds present in palm oils help reduce the oxidation of oils. Dietary supplementation with palm oils, particularly CPO and RPO, contributed to the lower liver, serum and jejunal mucosal antioxidant enzyme activities. The antioxidant enzyme genes in the jejunal mucosa were downregulated in palm oils and PKO, but there was no difference between oils in antioxidant enzyme genes in the liver. In conclusion, dietary supplementation with oils with high antioxidant content contributed to protection against oxidation and was associated with a lower requirement for producing antioxidant enzymes.